Zagadnienie poziomu agregacji danych w metodach wyborów dyskretnych - Rybicka, Aneta; Bartłomowicz, Tomasz (Problem of Data Aggregation Level in Discrete Choice Models, 2009)
The paper presents a decompositional approach to measurement of consumers' preferences: conjoint analysis methods and discrete choice methods. The utilities are estimated at individual level in conjoint analysis. In discrete choice methods utilities are estimated at aggregate level, but with latent class models we can estimate them at segmentation level. In order to estimate utilities at individual level there should be used hierarchical Bayes models. In the article, the basic characteristics of latent class models and hierarchical Bayes models as well as the benefits of their use in discrete choice methods were described. Additionally, software being used with both kinds of models was presented. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 375-381